Supplemented spaces of the functions on the Peano continua - Bazilevich , L. E. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A description of the topology of the pair (C (Π, I), C (Π, I)) for the Peano continuum Π, where C (Π, I) is the closure in the hyperspace ехр (Π × I) of the image of the space of continuous functions C (Π, I) under the natural embedding, is obtained.